2020
DOI: 10.3389/fmars.2020.00490
|View full text |Cite
|
Sign up to set email alerts
|

Benthic Communities on the Mohn’s Treasure Mound: Implications for Management of Seabed Mining in the Arctic Mid-Ocean Ridge

Abstract: The Mohn's Treasure, described as an inactive sulfide mound, was discovered at 2,600m depth on the Arctic Mid-Ocean Ridge (AMOR) in 2002. In 2015, we conducted the first biological survey of Mohn's Treasure using remotely operated vehicle (ROV) photo transects and sampling. This site is covered by a thick layer of fine sediments, where hard substratum is only visible as rocky outcrops on ridges. The observed benthic community was typical of Arctic bathyal systems. A total of 46 species (identified as morphospe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 37 publications
3
10
0
Order By: Relevance
“…, C. arcticus ) and their associates adapted to comparatively colder Arctic water; and shallower areas with a more diverse megafauna likely benefiting from a dynamic mixing between water masses supplying oxygen and nutrients, as well as preventing high sedimentation. The findings in the ARS are supported by previous observations from neighboring ridges and straits ( Meyer et al, 2016 ; Roberts et al, 2018 ; Meyer et al, 2019 ; Ramirez-Llodra et al, 2020 ).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…, C. arcticus ) and their associates adapted to comparatively colder Arctic water; and shallower areas with a more diverse megafauna likely benefiting from a dynamic mixing between water masses supplying oxygen and nutrients, as well as preventing high sedimentation. The findings in the ARS are supported by previous observations from neighboring ridges and straits ( Meyer et al, 2016 ; Roberts et al, 2018 ; Meyer et al, 2019 ; Ramirez-Llodra et al, 2020 ).…”
Section: Discussionsupporting
confidence: 90%
“…The sponge aggregations observed during our study of the ARS are similar to the ones found on the Schulz Bank located on the transition between the Mohn and Knipovich ridges ( Roberts et al, 2018 ; Meyer et al, 2019 ) as well as on the Mohn’s Ridge ( Ramirez-Llodra et al, 2020 ), and, to some extent, in the eastern Fram Strait ( Meyer et al, 2016 ). These Arctic deep-sea habitats are known to have particular ecological significance, playing key roles both in the recycling of major nutrients ( Rooks et al, 2020 ), and serving as refuge and nursery areas for several demersal fish species such as the Arctic skate ( Amblyraja hyperborean [Collett, 1879]), the Roughhead grenadier ( Macrourus berglax Lacepède, 1801) and the Greenland halibut ( Reinhardtius hippoglossoides [Walbaum, 1792]) ( Meyer et al, 2019 ).…”
Section: Discussionsupporting
confidence: 82%
“…RAS could also help those in remote areas to access basic services, with examples ranging from how “ early childhood remote diagnosis and consultation may reduce mortality” to delivering medical supplies, blood or vaccines 38 , or improving education 30 . Furthermore, RAS could facilitate environmental conservation and research in inaccessible locations 39 . Even in seemingly accessible locations such as cities, participants thought that RAS could manage features that are otherwise expensive, dangerous or difficult for humans to access, such as vertical farms 40 or green walls/roofs.…”
Section: Resultsmentioning
confidence: 99%
“…The negative impact of unmanned aerial vehicles on birds is well-documented 54 . Participants envisaged scenarios where large-scale RAS-deployment would intensify such disruptions and cause comparable issues with other taxonomic groups, including some that are currently poorly known or isolated due to their inaccessible habitats, such as deep-sea organisms 39 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation